FAKTOR- FAKTOR YANG MEMPENGARUHI KUALITAS PEMBELAJARAN GURU MADRASAH TSANAWIYAH NEGERI DI KABUPATEN KEBUMEN (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The Influence of the Principal Leadership, Academic Supervision and the Teachers’ Work Motivation on the Teaching Quality of State Islamic Junior Secondary School (MTsN) Teachers in Kebumen Regency. The purpose of this study was to determine: a) the influence of the principal leadership, the academic supervision and teachers’ work motivation on teaching quality collectively, b) the influence of the principal leadership on the teaching quality, c) the influence of the academic supervision on the teaching quality, d) the influence of teachers' work motivation to the teaching quality. This research is quantitative research that used survey method. As the subjects or the population studied as many as 425 the state Islamic junior secondary school teachers (MTsN) in Kebumen Regency, while as many as 193 samples studied teachers, the technique used in this study is proportional random sampling technique. In the process of data collection, it was used questionnaires and in analyzing the data, it was used a model of multiple regressions with three predictors. The hypothesis testing of all variables collectively was used the F-test, followed by hypothesis testing each variable or individual used partial test (t-test). For data processing used SPSS v.16. In processing the data, it was sought contribution effectively together for all variables, i.e. by finding analysis determination coefficient multiplied by 100 % , while for seeking contribution effectively partially i.e. by multiplying the value of the Standardized Coefficient with value Correlated Zero-order multiplied by 100 % for each variable independently. Based on the results of hypothesis testing, both with technical analysis of multiple regression or partial regression that test with the t-test or ANOVA , showed that principal leadership, academic supervision and of teachers’ work motivation collectively have a positive influence and significant impact on the quality of teaching. The magnitude of the effective contribution collectively is 35.01 %, while the effective contribution of the individual is: a) principal leadership on the teaching quality is 21.25 %, b) principal academic supervision on the teaching quality is 6.47% and c) the teachers’ work motivation to the teaching quality is 7.29%.